1985
DOI: 10.1002/bjs.1800720919
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic detection of early and curable carcinoma of the gallbladder

Abstract: Five patients with early carcinoma of the gallbladder detected by ultrasonography were studied. Three complained of non-specific upper abdominal symptoms or were asymptomatic and two had severe biliary colic. Gallstones were present in the two patients without biliary symptoms. Early carcinoma of the gallbladder was demonstrated as a polypoid tumour by ultrasound in four patients and as thickening of the gallbladder wall in one. The tumour was over 2 cm in diameter in all but one patient in whom the tumour enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…21 The observation of the natural history of PLGs in one study showed that 95% of the lesions with a probable diagnosis of cholesterol polyps remained the same size or were shown to be benign lesions after cholecystectomy; in the other 5%, two thirds turned out to be adenoma or adenocarcinoma when they were resected. 22 The probable relationship between gallbladder adenoma and adenocarcinoma has been sustained by several authors, including Kosuka and others, 13,23 who in the histopathologic analysis of resected gallbladders determined the presence of transition from adenoma to carcinoma, the association of all carcinomas in situ with adenomas, the high frequency of residual adenoma in patients with invasive carcinoma, and an increase in size of lesions transforming from adenoma to carcinoma (benign adenomas were Ͻ12 mm, adenomas with carcinoma in situ were Ͼ12 mm, and invasive carcinomas were Ͼ30 mm). Koga et al 10 made a comparative analysis between benign and malignant lesions and found that 94% of benign lesions are smaller than 10 mm, whereas 88% of malignant lesions are larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…21 The observation of the natural history of PLGs in one study showed that 95% of the lesions with a probable diagnosis of cholesterol polyps remained the same size or were shown to be benign lesions after cholecystectomy; in the other 5%, two thirds turned out to be adenoma or adenocarcinoma when they were resected. 22 The probable relationship between gallbladder adenoma and adenocarcinoma has been sustained by several authors, including Kosuka and others, 13,23 who in the histopathologic analysis of resected gallbladders determined the presence of transition from adenoma to carcinoma, the association of all carcinomas in situ with adenomas, the high frequency of residual adenoma in patients with invasive carcinoma, and an increase in size of lesions transforming from adenoma to carcinoma (benign adenomas were Ͻ12 mm, adenomas with carcinoma in situ were Ͼ12 mm, and invasive carcinomas were Ͼ30 mm). Koga et al 10 made a comparative analysis between benign and malignant lesions and found that 94% of benign lesions are smaller than 10 mm, whereas 88% of malignant lesions are larger than 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in the almost cases, the surgeon can perfectly suspect this cancer after opening the gallbladder. It is macroscopically apparent on the mucosa of the gallbladder in almost cases [2,3,6,7,11,12]. In our series, it was the case (macroscopically visible) in 29 cases (87.8%) after the opening of the gallbladder by the surgeon.…”
Section: Discussionmentioning
confidence: 44%
“…The prognosis of this form of gallbladder cancer is excellent with a cholecystectomy [2,11,14,16,18] and radical cholecystectomy. The 5 year survival fluctuates between 70% and 100% [2,7,8,11,14,[16][17][18][19][20][21]26]. In our experience, we encountered one death (radical cholecystectomy) not related to the surgery (myocardial infarction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Piehler and Crichlow [1], the surgeon will encounter cancer in approximately 1.9% of the operations of the biliary tract. Ultrasound helps in early detection and treatment of gall bladder cancer [2], Most patients are operated upon with a preoperative sonographic diagnosis of gallstones or acute cholecystitis, the operative finding being extensive carcinoma of the gallbladder, sometimes with massive hepatic involvement. Though ultrasound is the imaging tool most widely used, other techniques include com puted tomography (CT), percutaneous transhepatic chol angiography (PTC) and endoscopic retrograde cholangio Normal values: bilirubin < 1.0 mg%; LDH <225 U/l; SGOT <40 U/l.…”
Section: Introductionmentioning
confidence: 99%